Topographies of the Obsolete: Ashmolean Papers - Mydland, Anne Helen; Brownsword, Neil (UK Topographies of the Obsolete Publications, 2017)
In The Natural History of Staffordshire, Dr Robert Plot, the first keeper of the Ashmolean Museum describes an early account of the countys pre-industrial pottery manufacturing during the late 17th century. Apart from documenting potters practices and processes, Plot details the regions natural clays that were once fundamental to its rise as a world renowned industrial centre for ceramics. Yet in recent decades the factories and communities of labour that developed around these natural resources have been subject to significant transition. Global economics have resulted in much of the regions ceramic industry outsourcing to low-cost overseas production. Today, despite the City of Stoke-on-Trents ongoing regeneration, the economic fallout and human cost of the decline of traditional industry remain prevalent throughout its six towns. Plots pre-industrial mapping of North Staffordshire in the 1680s, has been echoed through Topographies of the Obsolete, an artistic research project which surveys the regions post-industrial landscape through a range of multi-media responses, centred primarily around the former Spode factory. Following six on-site residencies, Topographies has framed a point in time through which artists have opened different perspectives to the complexities of deindustrialisation, addressed by politicians, economists, historians and ex-employees.This publication, the fourth in the series, draws together and extends the proceedings from this symposium at the Ashmolean Museum of Art and Archaeology, University of Oxford. It offers a broad range of interdisciplinary insights into issues surrounding the impact of deindustrialisation upon heritage, communities and landscapes, and urban renewal through art and culture-led strategies.